Angiotensin II induces skin fibrosis: a novel mouse model of dermal fibrosis - Stawski, Lukasz (BioMed Central, 2012)
INTRODUCTION: Systemic sclerosis (SSc) is an autoimmune inflammatory disorder of unknown etiology characterized by fibrosis of the skin and internal organs. Ang II (angiotensin II), a vasoconstrictive peptide, is a well-known inducer of kidney, heart, and liver fibrosis. The goal of this study was to investigate the profibrotic potential of Ang II in the mouse skin. METHODS: Ang II was administered by subcutaneous osmotic mini pumps to C57BL/6 male mice. Collagen-content measurements were performed with Gomori Trichrome staining and hydroxyproline assay. The mRNA expression level of collagens, TGF-β1, TGF-β2, TGF-β3, CTGF, αSMA, CD3, Emr1, CD45/B220, MCP1, and FSP1 were quantified with real-time polymerase chain reaction (PCR). Immunostaining was performed for markers of inflammation and fibrosis, including, phospho-Smad2, αSMA, CD3, Mac3, CD45/B220, and CD163B. Fibrocytes were identified by double staining with CD45/FSP1 and CD45/PH4. Endothelial cells undergoing endothelial-to-mesenchymal transition (EndoMT) were identified by double staining with VE-cadherin/FSP1. RESULTS: Ang II-infused mice develop prominent dermal fibrosis in the area proximal to the pump, as shown by increased collagen and CTGF mRNA levels, increased hydroxyproline content, and more tightly packed collagen fibers. In addition, elevated mRNA levels of TGF-β2 and TGF-β3 along with increased expression of pSmad2 were observed in the skin of Ang II-treated mice. Dermal fibrosis was accompanied by an increased number of infiltrating fibrocytes, and an increased number of αSMA-positive cells, as well as CD163B(+ )macrophages in the upper dermis. This correlated with significantly increased mRNA levels of αSMA, Emr1, and MCP1. Infiltration of CD3-, CD45/B220-, and Mac3-positive cells was observed mainly in the hypodermis. Furthermore, an increased number of double-positive VE-cadherin/FSP1 cells were detected in the hypodermis only. CONCLUSIONS: This work demonstrates that Ang II induces both inflammation and fibrosis in the skin via MCP1 upregulation and accumulation of activated fibroblasts. Additionally, our data suggest that populations of these fibroblasts originate from circulating blood cells. Ang II infusion via osmotic minipumps could serve as a useful mouse model of skin fibrosis to gain new insights into pathogenic mechanisms and to test new antifibrotic therapies.